Associations between cognitive function and marital status in the United States, South Africa, Mexico, and China - Elyse A. Jennings; Meagan T. Farrell; Yuning Liu; Livia Montana (Elsevier, 2022)
We investigate the associations between marital status and cognitive well-being among adults aged 50 and older across four settings: the United States, rural South Africa, Mexico, and China. Using a standardized measure of immediate word recall, we assess whether people in each non-married status have worse cognitive function than their married counterparts, and the extent to which these associations vary across settings. We theorize that the practices around marriage in each setting, as well as the social stigma attached to marital dissolution, will reveal differing associations between marital status and cognition. Results suggest that, among women, being in a widowed marital status is associated with lower cognitive function in each setting except Mexico (after accounting for education and employment), while being separated/divorced or never married is associated with lower cognitive function only among women in the U.S. and Mexico. Among men, being widowed is associated with lower cognitive function relative to being married in each setting except South Africa (after accounting for education and employment), and being never married is associated with lower cognitive function in the U.S. and China (but not in South Africa or Mexico, after accounting for education and employment). Men also face relatively lower cognitive function if separated/divorced in the U.S. and South Africa. We discuss possible reasons for these associations across settings.